An Ethnomatics-based Learning Innovation: A Literature Review - Mubarak, Rafiq; Mahmudah, Fitri Nur (EARR (Educational Administration Research and Review), 2020)
Mathematics learning that is used in the process of teaching and learning activities at school needs a novelty, namely utilizing local culture where students can connect with mathematics in everyday life so that they can instill a love of local culture and form character in students. 1) knowing ethnomathematics learning innovation; 2) To transform local cultural values as one of the means of building national character. The design that is used in this article is a literature review. Articles are collected through reference sources such as Springer Link, JSTOR, and Google Scholar. The criteria of articles that are used in the last six years, starting from 2014-2019 which produced a collection of 9 scientific articles. The analysis was carried out by collecting articles and reducing them according to the theme of the article. The first results show learning innovation with a local cultural approach so that students will easily implement mathematics with the local culture. The second is to instill local cultural values in learning. It will instill the character of love for the country and the nation.